Pemodelan dan Evaluasi Proses Bisnis menggunakan Business Process Improvement (BPI) (Studi Kasus : Bagian Humas Universitas Mataram) - Neneng Al-Anis Naudhatul Marik; Diah Priharsari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Public Relations of the University of Mataram is a part under the auspices of the University of Mataram which aims to become a center for information, publications and documentation. Mataram University Public Relations has 4 business processes including, information management processes, documentation management processes, regional keprotokan activity organizers, and administration administrators. While undergoing the business process, Public Relations of the University of Mataram still encounters various obstacles such as the difficulty of communication in the data collection process and difficulties in knowing the status of news. The hope of the Head of Public Relations at the University of Mataram is that by taking into account the assistance and utilization of the information system provided, existing business processes can run more efficiently in the future. From the problems that have been described, an analysis and improvement of the business process of information management is carried out. The analytical method used is Business Process Improvement (BPI), then the results of the analysis and evaluation will then be simulated on the business process. After conducting a simulation of information management business processes, it showed that there was a reduction in the total time for the business process being executed, namely the information management business process by 1060 minutes to 856 minutes. So it can be concluded that the time needed to carry out the recommendation business process is more efficient than the current business process at Mataram University Public Relations.